Artificial Organs - Hakim, Nadey S. (New Techniques in Surgery Series,, 2009)
Artificial Organs covers everything from the support of multiorgan failure, and blood substitutes, to the management of short bowel syndrome, artificial sphincters, and circulatory support in heart failure. Other issues covered include pancreatic substitution in case of diabetes, the dialysis machine in kidney failure, the bionic ear in deafness, skin substitutes in cases of burns, and stem cells in organ replacement. Written by experts from European and US, both physicians and surgeons, each of the chapters compares the artificial organ to what is currently available from the transplant point-of-view, to highlight the current and modern available techniques for organ replacement. The book is useful reading for surgeons, and those interested in modern surgical and medical technology. Professor Nadey S Hakim (KCSJ, MD, PhD, FRCS, FRCSI, FACS, FICS) Consultant Transplant & General Surgeon Surgical Director, Transplant Unit, Hammersmith Hospital.